2015
DOI: 10.1242/jcs.169623
|View full text |Cite
|
Sign up to set email alerts
|

ATF6a, a Runx2-activable transcription factor, is a novel regulator of chondrocyte hypertrophy

Abstract: Our previous research has shown that the spliced isoform of XBP1 (XBP1s) is an important downstream mediator of BMP2 and is involved in BMP2-stimulated chondrocyte differentiation. Herein, we report that ATF6 and its cleaved N-terminal cytoplasmic domain (known as ATF6a) are expressed in growth plate chondrocytes. We find that these proteins are differentially induced during BMP2-triggered chondrocyte differentiation. This differential expression probably results from the activation of the ATF6 gene by Runx2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 68 publications
0
18
0
1
Order By: Relevance
“…The factor, however, exacerbates post-traumatic osteoarthritis downstream of inflammatory cytokines. Other studies have suggested that ATF2 and CREB could promote GPC cell cycle progression, and that ATF6 could promote chondrocyte hypertrophy by interacting with RUNX2 [149]. BBF2H7 (encoded by CREB3L2 ) is a membrane-bound TF most highly expressed in CCs [150].…”
Section: Basic-domain Transcription Factorsmentioning
confidence: 99%
“…The factor, however, exacerbates post-traumatic osteoarthritis downstream of inflammatory cytokines. Other studies have suggested that ATF2 and CREB could promote GPC cell cycle progression, and that ATF6 could promote chondrocyte hypertrophy by interacting with RUNX2 [149]. BBF2H7 (encoded by CREB3L2 ) is a membrane-bound TF most highly expressed in CCs [150].…”
Section: Basic-domain Transcription Factorsmentioning
confidence: 99%
“…Recently, ATF6 has been implicated in the development of multiple tissue types, and dysregulation of ATF6 expression is related to disease (Hillary and FitzGerald, 2018). Developmental roles of ATF6 include mesoderm differentiation (Kroeger et al, 2018), osteogenesis and chondrogenesis (Guo et al, 2016;Jang et al, 2012;Kim et al, 2014;Maeda et al, 2015;Xiong et al, 2015), neurodevelopment (Cho et al, 2009;Naughton et al, 2015;Saito et al, 2012;Zhang et al, 2007), adipogenesis and lipogenesis (Lowe et al, 2012), and formation of female reproductive structures (Lin et al, 2012;Park et al, 2013;Xiong et al, 2016;Yang et al, 2015). Most relevant to our work is the role of ATF6 in ocular and muscular embryology, because these tissues had the highest ATF6 reporter expression during zebrafish development.…”
Section: Introductionmentioning
confidence: 99%
“…Then we draw a conclusion that XAT suppresses chondrocyte hypertrophic differentiation of MSCs. The transcription factor Runx2 is crucial for regulating chondrocyte hypertrophy ( 21 , 22 ). Overexpression of Runx2 in all chondrocytes resulted in premature chondrocyte hypertrophy ( 23 ).…”
Section: Discussionmentioning
confidence: 99%